(untitled) (Scientific journal of the Fergana State University, 2024)
It is known that any tourism activity is closely related to natural-geographical and hydrometeorological factors. Among such factors, a special place is occupied by the structure of the relief, climatic conditions, hydrography and vegetation of the area. Such factors make people interested in recreation areas. In addition, the work carried out as part of the development of tourism in our country, turning it into a priority area, requires research into the tourism potential of the regions. Taking into account the above circumstances, the main purpose of this article was to analyze the physical and geographical opportunities for tourism development in the Shakhimardansay basin. The work used special topographic, cartographic, geographical similarity and comparison, as well as landscape analysis methods. In the study, the physical and geographical features of the Shakhimardansay basin, that is, relief, hydrological and hydrometeorological conditions, were considered as a recreational resource, and as a result were assessed for the purpose of developing tourism in the basin. The final part of the work described the ongoing work to develop tourism in the Shakhimardansay basin and its prospects.